Review: Etnobotani, Toksisitas, Fitokimia, dan Aktivitas Biologi Dari Tumbuhan Renda (Carissa carandas L) - Fadhli, Haiyul; Difa, Faradini Ramsanjami; Frimayanti, Neni; Aryani, Fina (Jurnal Farmasi Udayana; Vol. 12, No. 2, tahun 2023DO - 10.24843/JFU.2023.v12.i02.p04, 2024)
Renda (Carissa carandas L.) is a plant in the Apocynaceae family with dichotomous branches and milky sap. The plant bears small, oval-shaped fruits that are green at first and turn reddish-purple as they ripen. This review aims to integrate the secondary metabolites and biological activities of Carissa carandas L while also providing the scientific evidence required for future research. Online and offline literature were used to review this article. Online literature is sourced from local and international journal publications from journal providers on the internet and from online literature in books and e-books. This article covers the ethnobotany, toxicity, secondary metabolite compounds, and biological activities reported through search engines such as Google Scholar, NCBI, PubMed, ScienceDirect, Research Gate, and Springer. Based on existing literature, Carissa carandas can help treat diabetes, hypertension, hepatoprotection, anticonvulsants, antimalarials, antioxidants, anthelmintics, diarrhea, and hyperlipidemia.